Retrospective Study Of Vitamin Purchases During The Pandemic In UMI FARMA Pharmacy - Manik, Umi Chairani; Nasution, Muhammad Amin; Octania, Adelia Dwi (Pustaka Media Publishing, 2023)
In early 2020, the world was shocked by the outbreak of a new pneumonia that started in Wuhan, China, and then spread rapidly to more than 190 countries and territories. This outbreak was named coronavirus disease 2019 (COVID-19), which is caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SA RS-CoV-2). The spread of this disease has had a broad social and economic impact.The COVID-19 pandemic that has occurred since March 2020 has affected all aspects of life. The aim of the research is to determine the purchase of vitamins during the pandemic in July–December 2021 at the UMI FARMA Pharmacy. This research was conducted retrospectively. Data collection was obtained from recording several vitamin products purchased by patients. Data was obtained from the sales and purchases book at the UMI FARMA Pharmacy. The targeted output is purchasing vitamins during the pandemic in July–December 2021.